2017
DOI: 10.1155/2017/7143547
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Psychological Variables and Sleep Quality in Students of Medical Sciences

Abstract: Objectives Students of medical sciences are exposed to many emotional and mental problems. In light of the importance of sleep quality in learning and liveliness, this study was conducted to examine the relationship between psychological variables (stress, anxiety, and depression) and sleep quality of students. Design This research is a cross-sectional analytical study, where all students studying at Fasa University of Medical Sciences in 2012-2013 year were selected. To examine the students' stress, anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
3
8
2
4
Order By: Relevance
“…Although these latter two studies (Fawzy and Hamed, 2017;Kalyani et al, 2017) included medical students only who may be exposed particular levels of emotional and physical stress, the results are consistent with other work indicating a link between sleep quality and anxiety.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although these latter two studies (Fawzy and Hamed, 2017;Kalyani et al, 2017) included medical students only who may be exposed particular levels of emotional and physical stress, the results are consistent with other work indicating a link between sleep quality and anxiety.…”
Section: Discussionsupporting
confidence: 86%
“…In a sample of nearly 500 Lebanese students Choueiry et al, (2016) observed that nearly 30% of students presented with clinically significant anxiety and that anxiety was significantly associated with sleep quality (Choueiry et al, 2016). Two independent studies in medical students (Fawzy and Hamed, 2017;Kalyani et al, 2017) reported high prevalence of moderate to severe anxiety (70% and 40%, respectively) which correlated with sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the findings of Papazisis et al (2014) 26. However, the results of some studies indicate a high level of depression among female students 27,29,30. Since educational stressors affect both sexes equally, there is a possibility of depression in both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Depression screening for nurses should start from studying in nursing, so that susceptible individuals can be identified and the progress of the disease can be prevented. 30 Furthermore, the presence of mental health counselors in the nursing workplace plays a vital role in the prevention of depression. 28 The study results recommend adopting a combined approach that includes both clinical tests and depression measurement tools in future research.…”
Section: Discussionmentioning
confidence: 99%